2009
DOI: 10.4049/jimmunol.0802906
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Latent HIV-1 Infection by the Periodontopathic Bacterium Porphyromonas gingivalis Involves Histone Modification

Abstract: Latently infected cells harbor the HIV-1 proviral DNA genome primarily integrated into heterochromatin, allowing the persistence of transcriptionally silent proviruses. Hypoacetylation of histone proteins by histone deacetylases (HDAC) is involved in the maintenance of HIV-1 latency by repressing viral transcription. In addition, periodontal diseases, caused by polymicrobial subgingival bacteria including Porphyromonas gingivalis, are among the most prevalent infections of mankind. Here we demonstrate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
141
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 75 publications
4
141
2
1
Order By: Relevance
“…High BA levels have been correlated with diseases (Imai et al 2012;Imai et al 2009;Margolis et al 1988) and apoptosis induction (Kurita-Ochiai and Ochiai 2010), whereas, low BA levels have been correlated with colonic health (Maslowski et al 2009;Wong et al 2006). BA levels detected in this study were relatively low as compared to those that are related to diseases (Imai et al 2012(Imai et al , 2009Margolis et al 1988), however, we hypothesize that cells exposed to low BA levels but with prolonged exposure time could still affect cellular function, in particular, mitochondrial function.…”
Section: Resultscontrasting
confidence: 46%
See 2 more Smart Citations
“…High BA levels have been correlated with diseases (Imai et al 2012;Imai et al 2009;Margolis et al 1988) and apoptosis induction (Kurita-Ochiai and Ochiai 2010), whereas, low BA levels have been correlated with colonic health (Maslowski et al 2009;Wong et al 2006). BA levels detected in this study were relatively low as compared to those that are related to diseases (Imai et al 2012(Imai et al , 2009Margolis et al 1988), however, we hypothesize that cells exposed to low BA levels but with prolonged exposure time could still affect cellular function, in particular, mitochondrial function.…”
Section: Resultscontrasting
confidence: 46%
“…BA levels detected in this study were relatively low as compared to those that are related to diseases (Imai et al 2012(Imai et al , 2009Margolis et al 1988), however, we hypothesize that cells exposed to low BA levels but with prolonged exposure time could still affect cellular function, in particular, mitochondrial function.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, few studies have successfully cultured this bacterium from oral specimens. It has also been observed that the periodontaldisease-associated bacteria Porphyromonas, Prevotella and Fusobacterium can produce butyric acid (Kurita-Ochiai et al, 2006) and, recently, Imai et al (2009) indicated that butyric acid is the major short-chain fatty acid (SCFA) produced by P. gingivalis. Our previous study demonstrated that the cell supernatants of C. butyricum strain MIYAIRI 588 inhibited survival of H. pylori (Takahashi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some reports indicated that H. pylori is a transient member of the oral microflora, since the growth of H. pylori in the oral cavity is influenced by various factors such as temperature, pH, oxidation-reduction potential, the availability of nutrients, flow of saliva and antimicrobial substances ( Okuda et al, 2000Okuda et al, , 2003. Furthermore, Imai et al (2009) indicated that P. gingivalis culture supernatant contained butyric acid in high concentrations, from 6.7 to 14.7 mM. Moreover, Margolis et al (1988) indicated that the concentration of butyric acid in dental plaque was in the range of 14.4 to 20.0 mM.…”
Section: Discussionmentioning
confidence: 99%